2015
DOI: 10.17159/sajs.2015/20140093
|View full text |Cite
|
Sign up to set email alerts
|

Sectoral electricity elasticities in South Africa: Before and after the supply crisis of 2008

Abstract: In this paper, we estimate the price elasticity of electricity for various industrial sectors of the South African economy from 2002 to 2011. The data used include sectoral electricity consumption data and electricity tariff data, both courtesy of Eskom as well as output data based on national statistics. The most important contribution this paper makes is that it includes the period after the sharp rises in electricity tariffs in 2007/2008 following a period of load-shedding and insecurity in electricity supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
5
13
0
Order By: Relevance
“…Therefore, this paper provides insight into the food-energy linkages within the overall nexus. This is also in accordance with the extensive literature on the water, food and energy nexus as highlighted in Smajgl, et al (2016) As argued by Narayan and Smyth (2005) and Blignaut et al (2015), reliable estimates of price and income elasticity of demand (like the ones calculated in this paper) are necessary when formulating and evaluating policies, especially those regarding household behaviour and the environment -particularly in the electricity sector. Thus, this study aims to estimate the long-run elasticities of residential demand for electricity in South Africa to understand and quantify the determinants of residential demand for electricity so in future we can accurately measure households' response to various energy related policy proposals such as the carbon tax and demand side management policies that aim at reducing electricity consumption in the residential sector.…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…Therefore, this paper provides insight into the food-energy linkages within the overall nexus. This is also in accordance with the extensive literature on the water, food and energy nexus as highlighted in Smajgl, et al (2016) As argued by Narayan and Smyth (2005) and Blignaut et al (2015), reliable estimates of price and income elasticity of demand (like the ones calculated in this paper) are necessary when formulating and evaluating policies, especially those regarding household behaviour and the environment -particularly in the electricity sector. Thus, this study aims to estimate the long-run elasticities of residential demand for electricity in South Africa to understand and quantify the determinants of residential demand for electricity so in future we can accurately measure households' response to various energy related policy proposals such as the carbon tax and demand side management policies that aim at reducing electricity consumption in the residential sector.…”
Section: Introductionsupporting
confidence: 87%
“…As presented in the background and literature review sections, the most common variables to use when estimating aggregate electricity demand include income, price of electricity, price of a substitute of energy and temperature variables. In this study, we estimate the determinants of residential electricity demand in South Africa at both the aggregate income level and at different income levels -low-, middle-and high--as a function of gross national disposable income, electricity prices, food prices and a dummy variable accounting for the possible impact of the 2007/08 load-shedding wave and the 2008 electricity price restructuring that South Africa experienced 6 . All variables -except the dummy -are in their natural logarithms.…”
Section: Methodology and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Although, previous literature mainly focused on the casual connection between the consumption of energy and growth in the economy (Bildirici et al, 2012;Destek & Aslan, 2017;Dogan, 2015;Ghali & El-Sakka, 2004;Ozturk, 2010;Polemis & Dagoumas, 2013;Wolde-Rufael, 2014;Wu et al, 2019). A sector specific relationship with electricity consumption is carried out between 1993-2006 and 1993-2011. The findings proposed that the irregular upsurge in the consumption of electricity is due to the structural changes in the production line (Blignaut et al, 2015;Inglesi-Lotz & Blignaut, 2011). Electricity consumption is usually more reactive to GDP (Bildirici et al, 2012;Ciarreta & Zarraga, 2010b, 2010aGhali & El-Sakka, 2004).…”
Section: Review Of Literaturementioning
confidence: 99%
“…In other words, income is a prevailing macroeconomic driver of electricity demand. Blignaut et al (2015) and utilised panel techniques to examine how sectors behaved in response to electricity consumption from 2002 to 2011 and 1993 to 2006 in South Africa. These studies found that output is more sensitive to electricity consumption than to electricity prices.…”
Section: Related Literaturementioning
confidence: 99%